Determination of parameters of electric magnetic field for presowing treatment of seeds of sunflower - Чёрная, Мария Александровна (Technology audit and production reserves, 2014)
Economic analysis shows, that now in Ukraine the average yield of agricultural crops has decreased by 20 – 25 %, including sunflower, due to the high cost and lack of mineral fertilizers and means of plant protection from pests. Therefore, the urgent task is the development of new cost-effective, efficient and environmentally safe technologies, aimed at improving the yield and quality of the seeds sunflower. One way of solving this problem is the use of information EMF EHF. In the work, on the basis of the developed model of sunflower seeds and theoretical research is by definition biotropic parameters bottom-kinergetics (information) electromagnetic fields millimet-metre wavelength range (frequency, the power flux-density, Expo-sure, amplitude modulation), which may have an impact on the biophysical processes in seeds. The use of the electromagnetic field, with established biotropic parameters for pre-sowing treatment of seeds, let yield and oiliness seeds of the new harvest.